Pengaruh Pola Kemitraan Perkebunan Kelapa Sawit Terhadap Pendapatan Petani di Kabupaten Bengkayang - Esidorus, Esidorus; Suyatno, Adi; Kurniati, Dewi (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2025)
Palm oil plays a strategic role in Indonesia